Myomectomy by Robotically Assisted Laparoscopic Surgery: Results at Foch Hospital, Paris - Asmar, Jennifer; Even, Marc; Carbonnel, Marie; Goetgheluck, Julie; Revaux, Aurelie; Ayoubi, Jean Marc (Frontiers in Surgery, 2015)
We reported an observational, retrospective chart review of 36 women underwent robotic myomectomy at the Department of Obstetrics and Gynecology, Foch Hospital. Short and long term results were analised. We compared our results with literature datas.